1999
DOI: 10.1351/pac199971010173
|View full text |Cite
|
Sign up to set email alerts
|

Countermeasures for Ice Covered Waters

Abstract: This chapter describes the state of knowledge regarding the most applicable countermeasures to deal with oil on, in or among ice. Countermeasures are discussed in the context of seasonal variations in ice conditions and observations of oil fate and behaviour in a variety of different situations. The behaviour of oil spilled in ice covered waters is governed largely by the ice concentration in the case of broken ice, and the processes of encapsulation and subsequent migration in the case of solid (fast) (ice). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, research and response experiences in sub-arctic and arctic areas have shown that low temperatures and ice can also enhance spill response and reduce environmental impacts under certain conditions (Shell et al 1983;Payne et al, 1991;Dickins and Buist 1999;Dickins 2004;Alaska Clean Seas 2005;SINTEF 2006;Allen and Dickins 2007;SL Ross 2007;;ExxonMobil Research and Engineering 2008). However, research and response experiences in sub-arctic and arctic areas have shown that low temperatures and ice can also enhance spill response and reduce environmental impacts under certain conditions (Shell et al 1983;Payne et al, 1991;Dickins and Buist 1999;Dickins 2004;Alaska Clean Seas 2005;SINTEF 2006;Allen and Dickins 2007;SL Ross 2007;;ExxonMobil Research and Engineering 2008).…”
Section: Oil Spill Planning and Response In Arctic And Cold Water Envmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research and response experiences in sub-arctic and arctic areas have shown that low temperatures and ice can also enhance spill response and reduce environmental impacts under certain conditions (Shell et al 1983;Payne et al, 1991;Dickins and Buist 1999;Dickins 2004;Alaska Clean Seas 2005;SINTEF 2006;Allen and Dickins 2007;SL Ross 2007;;ExxonMobil Research and Engineering 2008). However, research and response experiences in sub-arctic and arctic areas have shown that low temperatures and ice can also enhance spill response and reduce environmental impacts under certain conditions (Shell et al 1983;Payne et al, 1991;Dickins and Buist 1999;Dickins 2004;Alaska Clean Seas 2005;SINTEF 2006;Allen and Dickins 2007;SL Ross 2007;;ExxonMobil Research and Engineering 2008).…”
Section: Oil Spill Planning and Response In Arctic And Cold Water Envmentioning
confidence: 99%
“…Oil-spill response strategies and tactics for cold climates must be designed to deal with a mix of open water and ice conditions that could occur throughout any portion of the operating period (Dickins and Buist 1999). In cold regions, mechanical recovery strategies are based upon the deployment of large ice-strengthened vessels and barges, carrying high-volume skimmers, and the use of containment booms.…”
Section: Oil Spill Planning and Response In Arctic And Cold Water Envmentioning
confidence: 99%
See 1 more Smart Citation
“…SL Ross et al (2010), Brandvik (2007), Fingas and Hollebone (2002) and Dickins and Fleet (1992). In addition papers and reports by Dickins and Buist (1999), and Dickins et al (2000) describe the key processes associated with oil and ice interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Any increase in human activity in the ice‐covered waters could magnify the potential for an oil spill. At present we have no means to remotely detect oil under sea ice [ Emergency Prevention, Preparedness and Response Working Group , 1998; Arctic Monitoring Assessment Programme , 1998; Dickins and Buist , 1999; Dickins , 2000; U.S. Arctic Research Commission ( USARC ), 2004; DeCola et al , 2006]. This is a critical deficiency affecting all aspects of a response to an oil spill under ice [ USARC , 2004]; consequently research and development projects continue to focus on technologies and methods to improve oil spill response in ice‐infested waters [ DeCola et al , 2006].…”
Section: Introductionmentioning
confidence: 99%